Organizational structure of technical and tactical training of skilled goalkeepers in football - V.N. Shamardin; B.V. Khorkavyy (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to study the structure of technical and tactical training of skilled goalkeepers in football. Material : the study involved 40 goalkeepers in age from 21 to 39 years (team Premier League Championship of Ukraine). According to teacher's observations were under direct competition activity of skilled goalkeepers. Results : It is shown that the technical and tactical activities goalkeeper characterized by two phases of the game: action to protect and attack. In turn, they include eight typical situations. It was found that in accordance with these typical situations goalkeeper applying a technical and tactical actions. Conclusions : It is recommended to increase the efficiency of the game keeper in protective and offensive actions to use specific and non-specific exercises in a variety of standard situations arising during the match.